(a-2)*(a^2-4)/(a^2-4a-+4)化简!
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 06:53:16
(a-2)*(a^2-4)/(a^2-4a-+4)化简!(a-2)*(a^2-4)/(a^2-4a-+4)化简!(a-2)*(a^2-4)/(a^2-4a-+4)化简!(a-2)*(a^2-4)/(a
(a-2)*(a^2-4)/(a^2-4a-+4)化简!
(a-2)*(a^2-4)/(a^2-4a-+4)
化简!
(a-2)*(a^2-4)/(a^2-4a-+4)化简!
(a-2)*(a^2-4)/(a^2-4a+4)
=(a-2)*(a-2)*(a+2)/(a-2)^2
=(a-2)^2*(a+2)/(a-2)^2
=a+2
化简(a/a-2-a/a+2)×4-a/a(a/a-2-a/a+2)×4-a/a
5a-【a+(5a-2a)-2(a-3a)-4a】
a^2-4a
计算;(a^3)^4+a^10×a^2-a×a^2-a*a^3*a^8
a-2a+3a-4a+5a-6a+...+99a-100a
化简; a-2a+3a-4a+5a-6a+``````-2006a+2007a.
(a+3a+5a+...+2009a)-(2a+4a+6a+...+2008a)=
(a+3a+5a+.+2009a)-(2a+4a+6a+.2008a)
计算(a+3a+5a+...+2009a)-(2a+4a+6a+...+2010a)
(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=
化简:a-2a+3a-4a+5a-6a+.+2010a+2011a.
计算(a+3a+5a+.+2003a)-(2a+4a+6a+...+2004a)
(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
(a+3a+5a...+2009a)-(2a+4a+6a+...+2010a)=?
a(a-1)(a-2)(a-3)(a-4)因式分解
计算:(a+3a+5a+...+2013a)-(2a+4a+6a+...+2012a)=?
计算(a+3a+5a+.+2003a)-(2a+4a+6a+.+2004a)
【1】a+a=a×a a= [ ]【2】a×a=a÷a a=[ ]【3】a×a=a-a a=[ ] [4]a-a=a+a a=[ ]